2022
DOI: 10.1093/stcltm/szac004
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem/Stromal Cell Senescence: Hallmarks, Mechanisms, and Combating Strategies

Abstract: Aging is a multifaceted and complicated process, manifested by a decline of normal physiological functions across tissues and organs, leading to overt frailty, mortality, and chronic diseases, such as skeletal, cardiovascular, and cognitive disorders, necessitating the development of practical therapeutic approaches. Stem cell aging is one of the leading theories of organismal aging. For decades, mesenchymal stem/stromal cells (MSCs) have been regarded as a viable and ideal source for stem cell-based therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(77 citation statements)
references
References 226 publications
(204 reference statements)
0
75
2
Order By: Relevance
“…Particular attention was paid to the introduction of mes-2 of 22 enchymal stromal stem cells (MSC) into an organism experiencing problems caused by organ dysfunction as a result of physiological, (e.g., ischemia of different origin), chemical (drugs, poisons), biological (bacterial or viral invasion) or physical (hyperthermia, trauma) challenge. Admittedly, fetal MSC have the greatest therapeutic activity with an obvious loss of therapeutic properties as the host organism from which the MSC were isolated ages [1,2]. However, in any case, a serious limitation is the source of MSC and what is also important, obtaining it in an amount sufficient to afford the therapeutic effect, and this problem has not yet found a proper solution.…”
Section: Introductionmentioning
confidence: 99%
“…Particular attention was paid to the introduction of mes-2 of 22 enchymal stromal stem cells (MSC) into an organism experiencing problems caused by organ dysfunction as a result of physiological, (e.g., ischemia of different origin), chemical (drugs, poisons), biological (bacterial or viral invasion) or physical (hyperthermia, trauma) challenge. Admittedly, fetal MSC have the greatest therapeutic activity with an obvious loss of therapeutic properties as the host organism from which the MSC were isolated ages [1,2]. However, in any case, a serious limitation is the source of MSC and what is also important, obtaining it in an amount sufficient to afford the therapeutic effect, and this problem has not yet found a proper solution.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that senescence is associated with increased production of pro-inflammatory cytokines, such as IL-1 and IL-8, by senescent cells, collectively referred to as pro-inflammatory-associated SASP [ 34 ]. Notably, it is now evident that senescence can be transmitted to normal cells by SASP in a paracrine or autocrine manner [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The senescent state is primarily characterized by durable cell cycle arrest [ 34 , 38 ]. Activation of cyclin-dependent kinase (CDK) inhibitors p16 and p21 is essential for senescence-associated growth arrest, which antagonizes CDK to block cell cycle progression [ 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, oxidative stress, a higher rate of oxygen consumption, and genomic instability were all linked to MSC senescence. Thus, assessment of MSCs for percentage of aneuploidy cells before using them in clinical applications is recommended to decide how to combat MSC senescence [54,55]. Also, in vitro propagation of MSCs attenuates their capacity for cartilage regeneration ability and presents chromosomal morphological changes associated with potential anomalous karyotypes, which accelerate premature senescence [56].…”
Section: Genetic Materials Damagementioning
confidence: 99%